Identifying families' reasons for engaging or not engaging with childhood obesity services: A qualitative study. (June 2014) - Banks, Jonathan; Cramer, Helen; Sharp, Deborah J; Shield, Julian PH; Turner, Katrina M
The rise in childhood obesity in recent years has been accompanied by a number of initiatives to treat the condition. However, such interventions have often been characterised by poor levels of adherence to treatment and corresponding high attrition rates. This article presents data drawn from qualitative interviews to examine families' reasons for engaging or not engaging with child obesity services. Interviews took place with 15 families whose children attended a UK-based childhood obesity service and 17 families whose children withdrew from treatment. Our data suggested that involvement of children in the decision to attend a clinic was important in building engagement. Specialist diet and exercise advice tailored to individual family circumstance encouraged clinic engagement, but failed to engage some families who felt their personal circumstances had not been considered sufficiently. The clinic environment was viewed as not age appropriate for some children and did not match the expectations of some families. Our findings highlight the value of involving children in the decision to attend an obesity service and practitioners should, as much as possible, tailor advice to the circumstances of each family. Providing clinics for particular age groups in terms of environment and timing may enhance engagement with services.